2019
DOI: 10.1016/j.measurement.2018.09.030
|View full text |Cite
|
Sign up to set email alerts
|

Thermometry of intermediate level waste containers using phosphor thermometry and thermal imaging

Abstract: Intermediate level waste containers are used for the storage of an assortment of radioactive waste. This waste is heatgenerating and needs monitoring and so this work was undertaken to determine whether the mean internal container temperature can be inferred from the temperature of the vent. By using two independent thermometry techniquesphosphor thermometry and thermal imaging -the internal temperature was demonstrated to be proportional to the vent temperature as measured by both methods. The correlation is … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 6 publications
0
11
1
Order By: Relevance
“…Often powders are seeded into liquid and used to combine temperature and velocity maps [18], but they can also be mixed with a binder and applied to an object to measure surface temperature. Previous work has shown that there are MFG-binder combinations that are suitable for use in nuclear decommissioning and waste storage conditions [3] and that this phosphor coating can be used as an emissivity-free alternative to thermal imaging [2]. Phosphors have competing decay mechanisms-radiative by an electron change of energy level (photon) or thermal by lattice vibration (phonon).…”
Section: Phosphor Thermometrymentioning
confidence: 99%
See 1 more Smart Citation
“…Often powders are seeded into liquid and used to combine temperature and velocity maps [18], but they can also be mixed with a binder and applied to an object to measure surface temperature. Previous work has shown that there are MFG-binder combinations that are suitable for use in nuclear decommissioning and waste storage conditions [3] and that this phosphor coating can be used as an emissivity-free alternative to thermal imaging [2]. Phosphors have competing decay mechanisms-radiative by an electron change of energy level (photon) or thermal by lattice vibration (phonon).…”
Section: Phosphor Thermometrymentioning
confidence: 99%
“…Contact sensors can themselves be damaged by transmutation, and changes in the object being measured such as oxidation, corrosion, and densification can unpredictably alter, for example, heat-flux rate, contact thermal resistance and thermal radiance. Errors up to 20 • C even at a relatively low temperature of 80 • C have been reported for both thermocouples and radiation thermometers [2] This makes it difficult for those monitoring the waste to tell what might be a problem that needs addressing rather than what is a problem with thermometry.…”
Section: Introductionmentioning
confidence: 99%
“…McMillan et al (2019) monitored the internal container temperature of medium‐level waste containers that are utilized for radioactive waste disposal. The experimental results indicated that there is a linear relationship between the internal temperature and the vent temperature of the storage drum, based on thermal imagery and phosphor thermometry analysis.…”
Section: Container For Radioactive Waste Disposalmentioning
confidence: 99%
“…Recent laboratory-based measurements of an ILW container demonstrated a correlation between the temperature measured from internal contact thermometers and the external vent radiance temperature [2]. To understand the challenges applying these laboratory measurements to the ventilated engineered stores used, this experimental design was replicated in an environmental chamber to simulate the varying temperatures and high humidity typically experienced.…”
Section: Scope Of Workmentioning
confidence: 99%
“…A schematic of the ILW container can be seen in Fig. 1, the experimental conditions are identical to those in [2]. To supply heat to the container, two heaters were placed at the bottom of the container above the insulation layer, comprising both wooden blocks and multi-layer insulation.…”
Section: Container Configurationmentioning
confidence: 99%